Rate Dependence of the Compressive Response of Ti Foams - Nik Petrinic; Vito L. Tagarielli; Petros Siegkas; Louis-Philippe Lefebvre (Metals, 2012)
Titanium foams of relative density ranging from 0.3 to 0.9 were produced by titanium powder sintering procedures and tested in uniaxial compression at strain rates ranging from 0.01 to 2,000 s−1. The material microstructure was examined by X-ray tomography and Scanning Electron Microscopy (SEM) observations. The foams investigated are strain rate sensitive, with both the yield stress and the strain hardening increasing with applied strain rate, and the strain rate sensitivity is more pronounced in foams of lower relative density. Finite element simulations were conducted modelling explicitly the material’s microstructure at the micron level, via a 3D Voronoi tessellation. Low and high strain rate simulations were conducted in order to predict the material’s compressive response, employing both rate-dependant and rate-independent constitutive models. Results from numerical analyses suggest that the primary source of rate sensitivity is represented by the intrinsic sensitivity of the foam’s parent material.